2014
DOI: 10.1152/ajpheart.00516.2013
|View full text |Cite
|
Sign up to set email alerts
|

Integrated rate-dependent and dual pathway AV nodal functions: principles and assessment framework

Abstract: The atrioventricular (AV) node conducts slowly and has a long refractory period. These features sustain the filtering of atrial impulses and hence are often modulated to optimize ventricular rate during supraventricular tachyarrhythmias. The AV node is also the site of a clinically common reentrant arrhythmia. Its function is assessed for a variety of purposes from its responses to a premature protocol (S 1S2, test beats introduced at different cycle lengths) repeatedly performed at different basic rates and/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 73 publications
(110 reference statements)
1
16
0
Order By: Relevance
“…Interestingly, when applying these principles to His bundle recording, well-defined stable signals of good magnitude could be consistently recorded. 6 Despite the obviously smaller size of rabbit His bundle, these signals are typically larger and more neatly shaped than those obtained from humans with standard catheter electrodes regardless of their position. In this context, one may raise the question of whether current leakage is a limiting factor in standard large tip electrode.…”
Section: Why Do Smaller Electrodes Yield Larger Signals?mentioning
confidence: 96%
See 2 more Smart Citations
“…Interestingly, when applying these principles to His bundle recording, well-defined stable signals of good magnitude could be consistently recorded. 6 Despite the obviously smaller size of rabbit His bundle, these signals are typically larger and more neatly shaped than those obtained from humans with standard catheter electrodes regardless of their position. In this context, one may raise the question of whether current leakage is a limiting factor in standard large tip electrode.…”
Section: Why Do Smaller Electrodes Yield Larger Signals?mentioning
confidence: 96%
“…Perhaps, the Teflon withdrawal could favor a current leakage to the bath liquid that could become critical when studying small sources. Interestingly, when applying these principles to His bundle recording, well‐defined stable signals of good magnitude could be consistently recorded . Despite the obviously smaller size of rabbit His bundle, these signals are typically larger and more neatly shaped than those obtained from humans with standard catheter electrodes regardless of their position.…”
Section: Why Do Smaller Electrodes Yield Larger Signals?mentioning
confidence: 97%
See 1 more Smart Citation
“…The results showed that changes in AV node refractoriness, as reflected in the model parameter estimates, were in agreement with previous clinical findings. This suggests that the model parameters estimated from ECG during AF may be used as a surrogate for the AV node refractory period invasively assessed through a pacing protocol [7].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that changes in AV node refractoriness, as reflected in the model parameter estimates, were in agreement with previous clinical findings. This suggests that the model parameters estimated from ECG during AF may be used as a surrogate for the AV node refractory period invasively assessed through a pacing protocol [7].The purpose of the present study is to evaluate our model-based, non-invasive approach to assess AV node refractory periods during AF by comparing its estimates to the invasively assessed AV node refractory periods. Patients referred to the hospital for pulmonary vein isolation (PVI), being in AF upon arrival, are included in the study.…”
mentioning
confidence: 99%